Measuring the Efficiency of Islamic Social Finance Integration Models for MSME Empowerment - Nafiah Nafiah (PAPUA: International Journal of Sharia Business Management, 2025)
This study evaluates the efficiency of Islamic social finance integration models in strengthening Micro, Small, and Medium Enterprises (MSMEs) by combining zakat, waqf, and Islamic microfinance instruments into a unified empowerment framework. Using a multi-stage efficiency measurement approach based on Data Envelopment Analysis (DEA) and supported by institutional performance indicators, the research examines 30 Islamic social finance institutions across key Indonesian regions. Results reveal that integrated models significantly outperform single-instrument schemes in enhancing MSME productivity, capital resilience, and business continuity. Institutions adopting blended financing such as cash-waqf-backed microfinance, productive zakat funds, and revolving qard hasan portfolios achieve higher technical efficiency scores, with several reaching frontier performance. Key determinants of efficiency include governance quality, digital beneficiary assessment, and structured mentoring programs. The study offers empirical evidence that integration not only optimizes resource allocation but also accelerates MSME capability formation. These findings provide relevant policy implications for Islamic social finance regulators and practitioners seeking scalable and sustainable empowerment mechanisms.